Generation and Characterization of Immortalized Mouse Cortical Astrocytes From Wildtype and Connexin43 Knockout Mice - Cibelli, Antonio; Veronica Lopez-Quintero, Sandra; Mccutcheon, Sean; Scemes, Eliana; Spray, David C.; Stout, Randy F.; Suadicani, Sylvia O.; Thi, Mia M.; Urban-Maldonado, Marcia (Frontiers in Cellular Neuroscience, 2021)
We transduced mouse cortical astrocytes cultured from four litters of embryonic wildtype (WT) and connexin43 (Cx43) null mouse pups with lentiviral vector encoding hTERT and measured expression of astrocyte-specific markers up to passage 10 (p10). The immortalized cell lines thus generated (designated IWCA and IKOCA, respectively) expressed biomarkers consistent with those of neonatal astrocytes, including Cx43 from wildtype but not from Cx43-null mice, lack of Cx30, and presence of Cx26. AQP4, the water channel that is found in high abundance in astrocyte end-feet, was expressed at moderately high levels in early passages, and its mRNA and protein declined to low but still detectable levels by p10. The mRNA levels of the astrocyte biomarkers aldehyde dehydrogenase 1L1 (ALDH1L1), glutamine synthetase (GS) and glial fibrillary acidic protein (GFAP) remained relatively constant during successive passages. GS protein expression was maintained while GFAP declined with cell passaging but was still detectable at p10. Both mRNA and protein levels of glutamate transporter 1 (GLT-1) declined with passage number. Immunostaining at corresponding times was consistent with the data from Western blots and provided evidence that these proteins were expressed at appropriate intracellular locations. Consistent with our goal of generating immortalized cell lines in which Cx43 was either functionally expressed or absent, IWCA cells were found to be well coupled with respect to intercellular dye transfer and similar to primary astrocyte cultures in terms of time course of junction formation, electrical coupling strength and voltage sensitivity. Moreover, barrier function was enhanced in co-culture of the IWCA cell line with bEnd.3 microvascular endothelial cells. In addition, immunostaining revealed oblate endogenous Cx43 gap junction plaques in IWCA that were similar in appearance to those plaques obtained following transfection of IKOCA cells with fluorescent protein tagged Cx43. Re-expression of Cx43 in IKOCA cells allows experimental manipulation of connexins and live imaging of interactions between connexins and other proteins. We conclude that properties of these cell lines resemble those of primary cultured astrocytes, and they may provide useful tools in functional studies by facilitating genetic and pharmacological manipulations in the context of an astrocyte-appropriate cellular environment.